Studi Tentang Analisis Aliran Syiah Di Indonesia - Ari Arkanudin (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2021)
The existence of Shia groups in Indonesia, as in other areas outside Iran, is still not widely known. Even though some writers think that Shia have entered the archipelago since the beginning of the arrival of Islam and their influence is quite strong in the Islamic tradition in the archipelago. The Shia movement in Indonesia is monitored by the ICC Jakarta (Islamic Cultural Center), which is led by a director named Mohsen Hakimullah from Iran. ICC operates in two aspects, namely education and da'wah. Shia in Indonesia are Shia Imamiyah based in Iran. Later his followers in Indonesia called themselves Ahlul Bayt, which is essentially Shia Imamiyah.